A systematic review on long-term clinical impact in patients with iliofemoral deep vein thrombosis. (October 2021) - Charisis, Nektarios; Harb, Hussein; Harb, Muhammed; Labropoulos, Nicos
Objective: The aim of this systematic review was to investigate the long-term clinical impact of iliofemoral (IF) deep vein thrombosis (DVT) based on patient reported outcomes, physician administered test measures and compare medical to interventional treatment. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. Criteria for inclusion were patients with thrombus involving the common femoral vein or more proximal veins, ≥5-year follow-up and physician assessment. Data quality was assessed using the Robins-I tool and Cochrane tool. Results: Eight studies that fulfilled our criteria were deemed eligible and provided data for 499 patients. There were 230 patients who received medical treatment and 269 interventional. Two studies were randomized controlled trials and six observational. Venous claudication, where reported, was found in 7.7% (1/13) of interventionally treated patients and 21% (13/62) of medically treated patients. Long term symptom resolution was reported in 58% (18/31) and 24% (12/50) of interventionally and medically treated patients, respectively. Venous ulcers were seen in 5.5% (7/126) of medically treated patients and 5% (5/100)of interventionally treated patients. Conclusion: A wide range of signs and symptoms was reported at long-term. Interventional treatment appeared to be better than medical one but the evidence was weak. Given the significant lack of patient reported outcomes, objective testing and use of validated instruments, the results should be interpreted in context with these limitations. Data on long-term outcomes after IF DVT have been poorly reported and outcome criteria should be better defined in future studies.